Effect of packaging atmospheres on storage quality characteristics of heavily marbled beef longissimus steaks. (July 2016) - Yang, Xiaoyin; Zhang, Yimin; Zhu, Lixian; Han, Mingshan; Gao, Shujuan; Luo, Xin
Abstract: The objective of this study was to investigate the effects of modified atmosphere packaging (MAP) systems on shelf-life and quality of beef steaks with high marbling. Four packaging types were used including 80% O2 MAP (80% O2  + 20% CO2 ), 50% O2 MAP (50% O2  + 30% CO2  + 20% N2 ), carbon monoxide MAP (0.4% CO + 30% CO2  + 69.6% N2 ) and vacuum packaging (VP). Steaks were displayed under simulated retail conditions at 4 °C for 12 days. Purge loss, pH, color stability, oxidative stability and microbial counts were monitored. Aerobically packaged steaks exhibited a bright-red color at the first 4 days. However, discoloration and oxidation became major factors limiting their shelf-life to 8 days. Compared with aerobic packaging, anaerobic packaging extended shelf-life of heavily marbled beef steaks, due to better color stability, together with lower oxidation and microbial populations. Among all packaging methods, CO-MAP had the best preservation for steaks, with more red color than other packaging types. Highlights: Anaerobic packaging extended the shelf-life of heavily marbled beef steaks. CO-MAP had the best preservation effect due to more red color and lower oxidation. 50%O2 -MAP resulted in the lowest color stability during storage. Discoloration and oxidation indicated a shelf-life of 8 days for aerobic MAP steaks. Steaks in anaerobic MAP had at least 12 days shelf-life.